Concept study of optical configurations for high-frequency telescope for LiteBIRD - Hasebe, T; Kashima, S; Ade, PAR; Akiba, Y; Alonso, D; Arnold, K; Aumont, J; Baccigalupi, C; Basak, S; Beckman, S; Borrill, J; Boulanger, F; et al. (Springer Verlag, 2018)
The high-frequency telescope for LiteBIRD is designed with refractive and reflective optics. In order to improve sensitivity, this paper suggests the new optical configurations of the HFT which have approximately 7 times larger focal planes than that of the original design. The sensitivities of both the designs are compared, and the requirement of anti-reflection (AR) coating on the lens for the refractive option is derived. We also present the simulation result of a sub-wavelength AR structure on both surfaces of silicon, which shows a band-averaged reflection of 1.1–3.2% at 101–448 GHz.